Depauperate soil fungal populations from the St. Helena endemic Commidendrum robustum are dominated by Capnodiales. (June 2020) - Detheridge, A.P.; Cherrett, S.; Clasen, L.A.; Medcalf, K.; Pike, S.; Griffith, G.W.; Scullion, J.
Abstract: The island of St Helena is small and over 1900 km from the nearest continental landmass. A unique flora, including five endemic genera of Asteraceae, developed on the island. Plant communities have changed radically since ca. 1550, with deforestation and introduction of continental species leading to extinctions and large reductions in the range and abundance of endemic species. One of these species, Commidendrum robustum, an arborescent Asteraceae, persists in small relict populations where coverage has been continual, and is now the subject of a restoration programme. Here we analysed the fungal community, via soil eDNA metabarcoding (ITS2 and LSU loci), to test if the relict populations of C. robustum harbour an indigenous fungal community and whether communities under plantations of different ages resemble those on relict sites. Plant communities were also analysed using eDNA metabarcoding (ITS2 locus). Fungal composition showed significant differences in C. robustum stands of different ages (PERMANOVA analysis). Fungi in C. robustum soils were unusual in having very low abundances of Basidiomycota and being dominated by Capnodiales, an order of Ascomycota more commonly inhabiting leaf surfaces. SIMPER analysis revealed the differences between sites to be mainly due to variations in the species of Capnodiales present. Capnodiales abundance was linked to soil organic content. Fungal communities were most closely related to ground flora and soil factors; the relative abundance of the introduced grass Ehrharta erecta, organic matter and pH significantly associated with fungal community structure. Arbuscular mycorrhizal fungi (AMF) were present at low levels and there was no correlation with C. robustum sequence abundance, rather a correlation with the abundance of Poales hosts.